EFFECT OF THE STRANDS FIXITY PROFILE SHAPE ON THE FLEXURAL BEHAVIOR OF STEEL BEAMS - Rasheed, Mohammed; Mahmoud, Kamal; Yousif , Mustafa Ahmed; Abdullah, Ahmed F. (Journal of Engineering and Sustainable Development, 2024)
This study concerns the effect of the external prestressing strand shape profile on the flexural behavior of steel beams. Seven steel beams that have the same cross-section are strengthened by external strands fixed by using Saddle Points of Deviation (Deviators). Based on two criteria, beams tested are divided into two categories whether external prestressing with fixity strands is present. The first group includes only one beam as a reference, while the second group deals with beams strengthened by two external strands. Six samples have been separated according to the eccentricity for external prestressing at a jacking stress of 815 MPa. During testing, it was discovered that the moment-curvature responses at the bottom and top flange region were stiffer than those in the reference, and the degree of hardening increases with eccentricity increasing. However, failure occurs with a slight warning as a result of insufficient ductility. Due to the presence of external prestressing, the ultimate moment capacity is enhanced by approximately 6.1%, 31.7%, 38.5%, 57.6%, 29.4%, and 80.2% as compared to the reference. Finally, the radius of curvature at the top flange region for strengthening samples has grown by approximately -16.7%, 8.0%, -26.9%, 21.5%, 17.5%, and 17.4% as compared to the reference case. In contrast, the percentage of the radius of curvature at the bottom flange region for strengthened samples dropped to 24,9%, 73.9%, 83.2%, 83.6%, 69.2%, and 89.0%, respectively, with an increase in the eccentricity position as compared to the reference.